COMPARISON OF COLOR CHANGE IN GLASS IONOMER CEMENT (GIC) AFTER TOPICAL FLUORIDE APPLICATION Using Type II Conventional GIC and Topical Fluoride in Sodium Fluoride (NaF) and Acidulated Phosphate Fluoride (APF) Preparations - Ichrom Nahzi, Muhammad Yanuar; Erlita, Isyana; Fathiya Julianti, A.M. Dewi (Dentino, 2017)
ABSTRACKBackground : Conventional glass ionomer cement is an applicative material used in dentistry. Topical flouride is widely used as a preventive measure against caries; it is available in various forms, such as Sodium Flouride (NaF), Stannous Flouride (SnF2), and Acidulated Phosphate Flouride (APF). There are a few considerations in selecting which form to use, and one of them is the physical characteristic which may interact and change the color of previously placed conventional glass ionomer cement. Purpose : This study aimed to find out whether there was a difference of color change in conventional glass ionomer cement after topical fluoride application between NaF and APF form. Method : This study was a true experimental research using pre and posttest with control group design. There were 18 samples divided into 2 treatment groups and 1 control group. Each group had 6 samples. The measurement was carried out using optical spectrometer (OPT 101 type of photo detector) and microvolt digital. Result: The mean color change in conventional glass ionomer cement after APF and NaF topical application was 1,7300 mv and 0,4983 mv respectively. One way ANOVA test and post hoc LSD test results showed a significant difference (p<0.05). Conclusion : Discoloration on APF topical application was higher than NaF.Keywords : Acidulated Phosphate Fluoride (APF), discoloration of conventional glass ionomer cement, Sodium Fluoride (NaF), topical fluoride.